Two quasi-spherical molecules [1, 4-diazabicyclo(3.2.2)nonane]X (X = ClO4, ReO4) exhibit switchable phase transition, dielectric and second-harmonic-generation properties. (12th July 2022) - You, Xiuli; Rao, Wenjun; Han, Keke; Wang, Lingyu; Zhang, Mengxia; Wei, Zhenhong
Abstract : Two quasi-spherical molecules [3.2.2-Hdabc]X (1, 4-diazabicyclo[3.2.2]nonane = 3.2.2-dabcn, X = ClO4, ReO4 ) with a high phase transition temperature exhibited switchable phase transition as well as dielectric and SHG properties. Abstract : Often, the quasi-spherical molecule 1, 4-diazabicyclo[2.2.2]octane (2.2.2-dabco) is chosen to prepare switchable materials with a high phase transition temperature. We wished to reduce molecular symmetry but maintain a quasi-spherical shape. Hence, a similar molecule, 1, 4-diazabicyclo[3.2.2]nonane (3.2.2-dabcn), was used to react with equimolar amounts of HClO4 or HReO4 in aqueous solution. Two compounds [3.2.2-Hdabcn]X (X = ClO4, 1 ; ReO4, 2 ) with high phase-transition points at 418 K for 1 and 394.6 K and 419.2 K for 2, respectively, were isolated, in which one-dimensional cationic chains were connected by different types of hydrogen bonds. Differential scanning calorimetry and dielectric-permittivity measurements revealed that 1 and 2 showed switchable phase transition and dielectric anomalies. Compound 1 also showed a reversible second-harmonic-generation effect.